TRANSLATION ISSUES OF COMPLEX ANALYTICAL GRAMMATICAL FORMS (KONFERENSIYA, 2025)
This article investigates semantic, pragmatic, and stylistic issues that arise when translating complex analytical grammatical forms from English into Uzbek. The study focuses on the comparative analysis of the Perfect, Progressive, Perfect Progressive aspects, modal constructions, and periphrastic structures, highlighting the main difficulties encountered in identifying their accurate Uzbek equivalents. Drawing on theoretical insights and practical translation samples, the article proposes effective strategies for overcoming these challenges. The results show that typological differences between analytical and synthetic languages require careful consideration of context, aspectual nuances, and modality during translation.